(untitled) - Halberstam, David (New York, 1991)
What can we learn from the events of twentieth century? With the effects of the Cold War still evident in the global economy and the lives of everyday Americans, master journalist and historian David Halberstam sets out to answer this question. Halberstam’s perceptive The Next Century looks to the future by examining the past. From the rise of the Japanese economy to the startling changes that reshaped the Soviet Union and Eastern Europe, Halberstam argues that the American economy’s survival depends on the rededication and continued education of the American worker. As pertinent in today’s economy as it was when first published in 1991, The Next Century is a timeless call to arms, reminding us that we must continually better ourselves in order to compete on the world stage.
Keywords: Thế kỷ 21,Twenty-first century; Dự báo,Forecasts